The personalization of democratic politics and the challenge for political parties - Cross, William P. (William Paul) 1962-; Katz, Richard S.; Pruysers, Scott 1985- (Littlefield International, Ltd ECPR Press, 2018)
"Those interested in election campaigns, voting, gender, governance, legislative behaviour, and political parties will all find something of value in the contributions that follow"--Provided by publisher.